Synthesis, characterisation and engineering of thin films of ZSM-5 on alumina, quartz and sand supports - Msimang, Velaphi Zakhele (Department of Chemical Engineering, 2014)
Zeolite films supported on inert material are a novel type of catalyst that could provide interesting activity and selectivity properties. Such materials will see application in catalytic distillation as reactive packings and in novel low pressure drop catalytic reactors. This thesis studies the physical and reactive properties of thin ZSM-5 films supported on alumina, quartz and sand packings. The objective of this work is to evaluate the intrinsic catalytic properties of these materials by estimating the reaction-diffusion model parameters from the results of the tri-isopropylbenzene (TIPB) cracking and para-xylene (pX) isomerization probe reactions. These intrinsic model parameters are then correlated with respect to the physical analysis of the zeolite films. It is postulated that the zeolite films on all supports would be smooth and homogeneous, the model parameters would be independent of film thickness while the selectivity and activity would depend strongly on film thickness. Zeolite films were prepared on 3 supports (3mm quartz and alumina beads, and 0.2mm sand particles) using the seed film method. The samples are characterised SEM, 12 adsorption, XPS, EDX, and ICP-AES. SEM analysis indicated that four film thicknesses of 150, 350, 800, 2300 nm are prepared on each support. Results indicate that only the Quartz supported zeolite films could be characterised as smooth and homogeneous. The sand supported zeolite was subject to agglomeration during preparation. The alumina support contained surface pores and mobile cations which caused non-uniform film growth and deactivated the active sites during catalyst pre-treatment, respectively. The TIPB reaction, which estimated only the external activity of the catalyst, showed that, for smooth inert films (quartz, sand) and within experimental error, the rate constants remained constant with film thickness. In the case of alumina supports, the activity increased with increasing film thickness, conforming to a diffusion driven migration of N a + cations which is confirmed by EDX and reaction analysis. The pX isomerization estimates the overall activity and selectivity. Smooth, homogeneous films with plate like geometry were assumed in all cases in order to develop a simple one-dimensional reaction-diffusion model. The model provided an excellent description of the experimental data. Analysis shows that for smooth, homogeneous zeolite films (quartz, sand) the activity is independent of film thickness. The pX activity of the alumina film (i.e., the zeolite film supported on alumina beads), increased with increasing film thickness which corresponded to deactivation caused by migration of Na + ions. Although, diffusion limitations were present, the observed ortho-xylene selectivity enhancement and activity reduction with increasing film thickness did not conform to that predicted by the reaction-diffusion model. As a result, the diffusivity increased with increasing film thickness i.e. it was not possible to predict the variation of activity and selectivity with film thickness using a diffusion coefficient. This was attributed to the non-homogeneity of the zeolite film possibly as a result of variations in the growth orientation and, in the case of alumina supports, cation migration. Chemical Vapor deposition (CVD) of tetraethoxysilane (TEOS) onto the external surface of a sand supported zeolite served only to deactivate the catalyst without significant selectivity enhancements. This has been attributed to a bulk blocking effect, in which active sites (pore volume) are rendered inaccessible by CVD. It is concluded that zeolite supported films approximated as smooth, homogeneous supports by physical characterization may not necessarily be homogeneous for catalytic applications even when care is taken to ensure that the support is smooth and inert. Furthermore, the selectivity and activity variation with film thickness are considerably smaller than expected.